1984
DOI: 10.1016/0166-1280(84)80077-9
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical determination of molecular structure and conformation

Abstract: Restricted Hartree-Fock calculations have been carried out for 1,3,&cycloheptatriene, norcaradiene, lH-azepine, benzenimine (azanorcardiene), oxepine and benzene oxide (oxanorcaradiene) employing the STO-3G, 4-31G and 6-31G* basis sets. Theoretical geometries, conformations and barriers to ring inversion have been obtained and compared with the available experimental structural data. It has been found that the cyclotrienes possess a boat conformation with a constant admixture of 22% chair character leading to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 40 publications
(33 reference statements)
0
13
0
Order By: Relevance
“…Although the boat form prevails for the monocyclic heteropines 1 , 3 and 5 , Cremer et al showed that this represents an incomplete picture [4344]. In fact, they are “perturbed” boats with at least 22% chair character, leading to an almost similar boat puckering for all.…”
Section: Reviewmentioning
confidence: 99%
“…Although the boat form prevails for the monocyclic heteropines 1 , 3 and 5 , Cremer et al showed that this represents an incomplete picture [4344]. In fact, they are “perturbed” boats with at least 22% chair character, leading to an almost similar boat puckering for all.…”
Section: Reviewmentioning
confidence: 99%
“…However, rarely are dipole moments measured in the gas phase. Uncertainty in experimental data can be illustrated by considering the experimental dipole moment of aniline: there are 45 dimethylpyridine molecule also shows an exceptionally large deviation i n dipole moment, whereas t h e calculated dipole moments for pyridine, the picolines, and the lutidines are in good agreement with experimental values. Since we cannot postulate a reasonable explanation for these deviations a t this time, we suggest that redetermination of experimental data may be necessary.…”
Section: Comparison Between Experimental and Theoretical Dipole Momentsmentioning
confidence: 66%
“…No experimental evidence for the existence of the "chair" conformer has been found. However, calculations 14 suggest that cycloheptatriene possesses a "boat" conformation with a constant admixture of 23% "chair" character to the "boat" form. In cycloheptatriene the C 3 C 4 and the methylenic group are forced above the plane formed by C 1 C 2 C 5 C 6 , producing a "boat" conformer (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Electron diffraction 12 and X Abstract published in AdVance ACS Abstracts, November 1, 1997. microwave data 13 suggest that cycloheptatriene in the gas phase possesses the "boat" conformation, although the microwave spectrum 13 indicates the possibility that puckering of the ring may be important. The most stable calculated conformation 14 of cycloheptatriene is a "perturbed boat" conformation, which is a linear combination of 77% "boat" and 23% "chair" (Figure 1). The barrier for the ring inversion was calculated to be about 6 kcal/mol, 14 but no energies were determined for the puckering of cycloheptatriene from "boat" to "chair".…”
Section: Introductionmentioning
confidence: 99%